Characteristics of the layered polar mesosphere summer echoes occurrence ratio observed by EISCAT VHF 224 MHz radar - S. Ge; H. Li; T. Xu; M. Zhu; M. Wang; L. Meng; S. Ullah; A. Rauf (Annales Geophysicae, 2019)
Polar mesosphere summer echoes (PMSEs) are strong radar echoes observed in the polar mesopause during the local summer. Observations of layered PMSEs carried out by the European Incoherent Scatter Scientific Association very-high-frequency (EISCAT VHF) radar during 2004–2015 in the latest solar cycle are used to study the variations of the PMSE occurrence ratio (OR). Different seasonal behavior of PMSEs is found by analyzing the seasonal variation of PMSE mono-, double-, and tri-layer OR. A method was used to calculate the PMSE mono, double-, and tri-layer OR under a different electron density threshold. In addition, a method to analyze the correlation of the layered PMSE OR with the solar 10.7 cm flux index (F10.7) and geomagnetic K index is proposed. Based on it, the correlation of the layered PMSE OR with solar and geomagnetic activities is not expected to be affected by discontinuous PMSEs. It is found that PMSE mono-, double-, and tri-layer ORs are positively correlated with the K index. The correlation of the PMSE mono- and double-layer OR with F10.7 is weak, whereas the PMSE tri-layer OR shows a negative correlation with F10.7.